Actin is a binding protein for angiogenin. - Hu, G F (1993)
The 42-kDa angiogenin binding protein isolated previously has been purified to electrophoretic homogeneity. It has been identified as a member of the actin family by peptide mapping and partial amino acid sequencing. The interaction of bovine muscle actin with angiogenin is similar to that of the angiogenin binding protein. Angiogenin induces the polymerization of actin below the critical concentration for spontaneous polymerization. The interaction occurs both in solution and on a poly(vinylidene difluoride) membrane. It is inhibited by excess unlabeled angiogenin and also by platelet factor 4 and protamine, which are known inhibitors of angiogenesis. Two other angiogenic molecules, basic fibroblast growth factor and tumor necrosis factor alpha, bind to 125I-labeled actin and can be crosslinked by a water-soluble carbodiimide. Both actin and an anti-actin antibody inhibit the angiogenic activity of angiogenin in the chicken embryo chorioallantoic membrane assay. The results indicate that the angiogenin binding protein is a cell surface actin and suggest that the reaction between angiogenin and this actin is an essential step in the angiogenesis process induced by angiogenin.